Neonatal health care costs of very preterm babies in England: a retrospective analysis of a national birth cohort - Yang, M; Campbell, H; Pillay, T; Boyle, E; Modi, N; Rivero Arias, O (BMJ Publishing Group, 2023)
Objectives: Babies born between 27+0 and 31+6 weeks of gestation represent the largest group of very preterm babies requiring NHS care, however up-to-date cost figures for the UK are not currently available. This study estimates neonatal costs to hospital discharge for this group of very preterm babies in England.